PELAKSANAAN CONTRA LEGEM OLEH HAKIM PENJABARAN NILAI HUKUM PROGRESIF - Siska Dewi Gelgel, Luh Gede; Sarjana, I Made (Kertha Semaya : Journal Ilmu Hukum, 2013)
Basically the judge to apply the law in accordance with existing rules. One of the principles of procedural law is prohibited judge rejected the case, however, the problems that arise when a lawsuit has no rule of law. This is where the judge is required to create law by digging the legal values that live in the community. The verdict set aside existing legislation is called contra legem. Translation of Contra legem a progressive implementation of legal value which requires fair laws that are not only focused on legalistic rule of law. The objective of the study was to determine the relationship between the implementation of the contra legem by judges with a progressive approach to law. In this paper, using the method of normative deskriptif.pendekatan the normative legal research using secondary data sources, while the descriptive approach to the method of research that seeks to describe and interpret objects in accordance with what it is.
Keywords: Progressive Law, Contra legem, Judge